印尼学生汉语课堂游戏设计 - Octi Rjeky Mardasari; Zhao Yanhua (Universitas Negeri Malang, 2022)
在印尼的第二语言教学中，很多本土外语老师还在使用语法翻译法来教外语，本土汉语老师也不例外，所以许多印尼学生对汉语学习兴趣不大。印尼学生经常对老师说，汉语课堂特别无聊、学汉语特别难、教学方法很落后等，以上问题都是印尼学生经常反映的问题。为了激发学生对汉语的兴趣、吸引学生的注意力，教师应该更新自己的教学方法。针对这种情况，利用课堂游戏来进行教学，可以说是一个值得尝试的途径，并且课堂游戏也是一个可以普遍应用于各种课型的教学手段。鉴于“课堂游戏”这一教学形式具有较为重要的教学地位，本文即以“课堂游戏”作为切入点展开讨论。论文的研究目的在于针对印尼学生设计一些课堂游戏，而这些游戏一般都和印尼本地的为人熟知的游戏有关。希望这些游戏设计对汉语教学以及印尼学生的汉语学习能够有所帮助。 In Indonesia, in teaching foreign languages as a second language, many local foreign language teachers still use grammar-translation methods to teach foreign languages, and local Chinese teachers are no exception. Therefore, Indonesian students are not very interested in learning Chinese. Indonesian students often tell their teachers that Chinese classes are particularly dull, learning Chinese is particularly difficult, and teaching methods are very backward. Indonesian students frequently report the above problems. To stimulate students' interest in Chinese and attract students' attention, teachers should update their teaching methods. Because of this situation, using classroom games for teaching can be said to be a way worth trying. And classroom games are also a teaching method that can be widely used in various types of lessons. Given the relatively important teaching status of